Digging Deep – Governing subsurface uses for the German energy transition - Juliane Biehl; Johann Köppel; Julia Neugebauer; Gesa Geißler (Cleaner Production Letters)
The geological subsurface holds diverse use potentials, including raw material extraction, renewable energy storage, carbon sequestration, and waste storage. While global resource governance is often emphasised, comprehensive synoptic overviews of specific subsurface uses and their environmental and social impacts are lacking. Given the climate crisis, sustainability goals, and recent geopolitical shifts, the European Union has intensified efforts to secure domestic raw materials to reduce dependency and support the energy transition. Within this context, Germany, the EU's most populous and economically influential member, provided a critical case study for examining subsurface governance challenges. This study aimed to (i) synthesise impacts and pressures from multiple subsurface uses and (ii) identify respective governance, planning, impact assessment (IA), and permitting gaps. A configurative literature review was conducted, reviewing academic literature, grey literature, policy reports, and IA documents for various subsurface activities, including mineral extraction, geothermal energy, carbon dioxide sequestration and hydrogen storage in Germany. Findings revealed cumulative environmental and social pressures, with significant impacts on land and water resources, and gaps in IA practices, such as limited consideration of population impacts, land degradation, and subsurface biodiversity. Increased spatial competition for subsurface space, including space for energy storage and waste management, heightened regulatory pressures. The study concluded that IA practices are often assumption-based, lacking long-term empirical data and that certain subsurface activities are inadequately assessed. Critical governance gaps are identified, suggesting entry points for enhancing environmental planning, impact assessments, and governance strategies in Germany's subsurface resource management.